Proceedings of SPE Annual Technical Conference and Exhibition 2004
DOI: 10.2523/90450-ms
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Casing-Cement-Formation Interactions Under Stress Conditions: Impact on Long-Term Zonal Isolation

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThe investigation of cement integrity over life of well conditions continues to be a high priority within the well cementing industry. Increasing awareness of problems associated with cement sheath failure and subsequent loss of zonal isolation or sustained casing pressure have demanded that set cement material behavior and the coupled behavior of casing, cement and formation be more fully understood in order to make rational engineering decisions. Recent adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…A numerical wellbore stress model was run to illustrate the different performances of each cement system for an identical well scenario. The model predicts likely cement sheath failure as a pass-fail feature based on maximum calculated stress compared to the known strength of the cement as described by Mueller et al (2004) and Myers et al (2005). The model assumes that casing, cement, and formation are linear elastic, isotropic, and homogeneous as well as mechanically coupled.…”
Section: "Conventional"mentioning
confidence: 99%
“…A numerical wellbore stress model was run to illustrate the different performances of each cement system for an identical well scenario. The model predicts likely cement sheath failure as a pass-fail feature based on maximum calculated stress compared to the known strength of the cement as described by Mueller et al (2004) and Myers et al (2005). The model assumes that casing, cement, and formation are linear elastic, isotropic, and homogeneous as well as mechanically coupled.…”
Section: "Conventional"mentioning
confidence: 99%
“…While some researchers develop computational techniques based on simplifications such as assumptions of linear elasticity, axisymmetric geometry or lack of cement shrinkage [14,15], most of the proposed computational methods recognize the necessity to encompass interaction of all components of the well as well as to include the entire loading history in order to obtain valid information about the state of stress in the cement sheath at a given time and given location. Some workers choose to develop or employ analysis techniques which lack detailed analysis of the stress state of casing, cement and formation, but concentrate more on the loading history, such as the Stress Analysis Model (SAM) described and applied in references [13,12,16,17] or the System Response Curve (SRC) technique as proposed in reference [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was observed that dynamic mechanical properties are considerably larger than the static ones. A significant difference between cement Young's modulus in tension and compression was discussed by Mueller et al (2004). ASTM methods were applied by Heinhold et al (2002) for measuring cement flexural and tensile strengths.…”
Section: Introductionmentioning
confidence: 99%